The role of kidney diffusion tensor magnetic resonance imaging in children - Mehmet Burak Özkan; Robert Marterer; Sebastian Tscheuner; Utku Mahir Yildirim; Elif Ozkan (The Egyptian Journal of Radiology and Nuclear Medicine, 2016)
Background: Diffusion tensor imaging (DTI) in magnetic resonance imaging (MRI) provides information about the microstructure of renal tissue and is becoming increasingly useful in the evaluation of relationship between renal structure and function. Objectives: To investigate, whether DTI allows assessment of renal impairment and pathology in pediatric patients with decreased renal functions. Materials and methods: Thirty-two pediatric patients and seventeen healthy children were included in this prospective study. For DTI, a respiratory-triggered coronal echo planar imaging (EPI) sequence was performed. Cortical and medullary mean axial and radial diffusivity and fractional anisotropy (FA) were analyzed. Results: In healthy subjects, the cortical FA values were significantly lower than the medullary FA values (p < 0.001). Cortical and medullary ADC values showed positive correlations (r = 0.499, p = 0.041) and a negative correlation with cortical FA values(r = −0.533, p = 0.028). The eGFR values were negatively correlated with the medullary ADC values (r = −0.484, p = 0.049) in healthy subjects and positively correlated with the λ medullary values (r = 0.385, p = 0.027). Additionally in the patient group, the age was positively correlated with FA cortex values (r = 0.411, p = 0.018) and with the medullary ADC values (r = 0.461, p = 0.007). However, the medullary FA values were negatively correlated with the medullary ADC values (r = −0.363, p = 0.038). Tractography of healthy volunteers showed a radial arrangement which converged into the pyramids, whereas renal insufficiency patients had irregular arrangement patterns and architectural distortions in the observed areas. Conclusions: Renal DTI is a promising diagnostic tool in the assessment of microstructural renal changes and correlates with the eGFR. Therefore, it is possible to estimate the arrangement of the tracks which emanate from the renal medulla. Furthermore, diffusion of the water molecules could be carried out. This study demonstrates the usage of DTI in renal pediatric kidneys. Validations in larger cohort groups with histopathological biopsies are needed.